Heterogeneous seismic anisotropy beneath Madeira and Canary archipelagos revealed by local and teleseismic shear wave splitting - Schlaphorst, David (2023)
Mid-plate upward mantle flow is a key component of global mantle convection, but its patterns are poorly constrained. Seismic anisotropy is the most direct way to infer mantle flow as well as melt distribution, yet the convection patterns associated with plume-like mantle upwelling are understudied due to limited seismic data coverage. Here, we investigate seismic anisotropy beneath the Madeira and Canary hotspots using a dense set of shear wave splitting observations and combining teleseismic and local events recorded by three-component broad-band and short-period seismic stations. Using a total of 26 stations in the Madeira archipelago and 43 stations around the Canary Islands, we obtain 655 high-quality measurements that reveal heterogeneous flow patterns. Although local event results are sparse around most islands, we can observe a small average of S-wave splitting times of 0.16 ± 0.01 s, which significantly increase with source depth beneath El Hierro (>20 km) and Tenerife (>38 km) up to 0.58 ± 0.01 and 0.47 ± 0.05 s. This suggests an influence of melt pocket orientation in magma reservoirs developed at uppermost-mantle depths. Likewise, anisotropy increases significantly beneath the islands with shield stage volcanism (up to 9.81 ± 1.78 per cent at El Hierro, western Canaries, against values up to 1.76 ± 0.73 per cent at Lanzarote, eastern Canaries). On average, teleseismic SKS-wave splitting delay times are large (2.19 ± 0.05 s), indicating sublithospheric mantle flow as the primary source for anisotropy in the region. In the Canaries, the western islands show significantly smaller average SKS delay times (1.93 ± 0.07 s) than the eastern ones (2.25 ± 0.11 s), which could be explained by destructive interference above the mantle upwelling. Despite complex patterns of fast polarization directions throughout both regions, some azimuthal pattern across close stations can be observed and related to present- day mantle flow and anisotropy frozen in the lithosphere since before 60 Ma. Additionally, we infer that the current presence of a mantle plume beneath the archipelagos leads to the associated complex, small-scale heterogeneous anisotropy observations.